In search of nature - Wilson, Edward O. (Washington, D.C. : Island Press, 1996)
Perhaps more than any other scientist of our century, Edward O. Wilson has scrutinized animals in their natural settings, tweezing out the dynamics of their social organization, their relationship with their environments, and their behavior, not only for what it tell us about the animals themselves, but for what it can tell us about human nature and our own behavior. He has brought the fascinating and sometimes surprising results of these studies to general readers through a remarkable collection of books, including The Diversity of Life, The Ants, On Human Nature, and Sociobiology. The grace and precision with which he writes of seemingly complex topics has earned him two Pulitzer prizes, and the admiration of scientists and general readers around the world.
This book is a lively and accessible introduction to the writings of one of the most brilliant scientists of the 20th century. Imaginatively illustrated by noted artist Laura Southworth, it is a book all readers will treasure.
Animal Nature, Human Nature. The Serpent. In Praise of Sharks. In the Company of Ants. Ants and Cooperation -- The Patterns of Nature. Altruism and Aggression. Humanity Seen from a Distance. Culture as a Biological Product. The Bird of Paradise: The Hunter and the Poet -- Nature's Abundance. The Little Things That Run the World. Systematics Ascending. Biophilia and the Environmental Ethic. Is Humanity Suicidal?
"A Shearwater book."
Includes bibliographical references (p. 201-202) and index.
Keywords: Philosophy of nature; Human beings; Human ecology -- Philosophy